Seismic Velocity Analysis for Improved Geopressure Modelling in Onshore Niger Delta - Bassey Umoren, Emmanuel; Daniel Uko, Etim; Tamunobereton-Ari, Iyeneomie; Israel-Cookey, Chigozie (International Journal of Advanced Geosciences, 2019)
In this study, an improved evaluation of pore pressure using a model based seismic inversion technique has been carried out. Across six wells in the Onshore Niger Delta Basin, post stack seismic volume, angle stack gathers, seismic horizons, check shot, wireline logs, drilling and pressure data were analysed and interpreted. The model based inversion technique was applied to improve the seismic resolution as well as derive acoustic impedance using well velocities along with stacking velocities from velocity analysis of the 3D seismic data. Bowersâ€™ Vp-VES coefficients of 7.43 and 0.77 were used to transform the derived seismic acoustic impedance velocity into seismic pore pressure cube. The seismic acoustic impedance interval velocity reveals much of the geology and resulted to a high resolution seismic pore pressure cube when compared at well location with direct pressure data. The Derived Seismic Pore Pressure (DSPP) also revealed that pore pressure and overpressure can reach or exceed 4000 and 1000psi respectively in the field. The results obtained have demonstrated that seismic acoustic impedance volume can offer high resolution seismic pore pressure cube in both time and space.Â Â